Design of micro-scale wind power plant with vertical axis wind turbine darrieus type-H - Yulianta Siregar; Ary Prayogo; Nur Nabila Mohamed; Issarachai Ngamroo (International Journal of Innovative Research and Scientific Studies, 2025)
In Medan Belawan District, Medan City, Indonesia, where average wind speeds are higher than in other districts, this proposal intends to build and simulate straight-blade wind turbines for use in micro-scale wind power plants as an alternative energy source. Given that the average annual wind speed in Medan Belawan District, Medan City, is 2.5 m/s, a wind turbine of the Darrieus rotor type-H, which is appropriate for regions with low wind speeds and fluctuating wind directions, can be developed. According to the design results, the turbine's height is 2.8 meters, and its diameter is 3.36 meters. Two Computational Fluid Dynamics (CFD) simulations of the turbine design were performed. In our conclusion, using SolidWorks software, the first generated a torque of 45.28 Nm, an average electrical power of 134.78 Watts, and a mechanical power of 168.48 Watts. The second generated an average mechanical power of 175.77 Watts, an average electrical power of 140.61 Watts, and a torque of 47.25 Nm using Ansys Fluent software.
Keywords: Vibration and Dynamic Analysis; Real-time simulation and control systems; Hydraulic and Pneumatic Systems